2022
DOI: 10.3390/plants11040507
|View full text |Cite
|
Sign up to set email alerts
|

Two MYB and Three bHLH Family Genes Participate in Anthocyanin Accumulation in the Flesh of Peach Fruit Treated with Glucose, Sucrose, Sorbitol, and Fructose In Vitro

Abstract: Anthocyanins are important pigments in peach fruit and are beneficial to human health. Sugars are both energy-storing and signaling molecules and their roles in inducing anthocyanin biosynthesis have received a great deal of research attention. However, the mechanism by which sugars induce anthocyanin biosynthesis in peach fruit is unknown. In order to understand this induction mechanism, comprehensive transcriptome and metabolome were performed in fruit flesh treated with four different sugars for 12 and 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…PPO4 relative expression and browning symptoms were slightly but significantly correlated at 28 + 2 d (r = 0.472 *). Similarly, Wang et al [ 27 ] reported that the PPO relative expression and browning symptoms were correlated in the “Yuhua” peach cv. after different periods of cold storage.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…PPO4 relative expression and browning symptoms were slightly but significantly correlated at 28 + 2 d (r = 0.472 *). Similarly, Wang et al [ 27 ] reported that the PPO relative expression and browning symptoms were correlated in the “Yuhua” peach cv. after different periods of cold storage.…”
Section: Resultsmentioning
confidence: 87%
“…Anthocyanins are flavonoids end-products with roles in plant resistance against biotic and abiotic stresses [ 27 ]. In addition, anthocyanin accumulation has been associated with bleeding [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the protein sequence revealed that the MrMYB9 protein contained a conserved R2R3 repeat, and the presence of a bHLH-binding domain in the R3 repeat segment of these proteins (Figure 5A) suggests a protein-protein interaction with bHLH TFs, as observed in previous research. Phylogenetic analysis positioned MrMY9 within a clade of FaMYB9-like co-activators in anthocyanin and proanthocyanidin pathways (Figure 5B) such as strawberry FaMYB9 [73], apple MdMYB308L [29], peach PpMYB6 [36], Arabidopsis thaliana AtMYB3 [74], AtMYB4 [75], and AtMYB32 [74]. Consequently, MrMYB9 exhibits all the structural features of known activators of anthocyanin and proanthocyanidin biosynthesis and may possess comparable regulatory functions.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a large number of MYB TFs controlling anthocyanin biosynthesis have been discovered in many plants. Activators responsible for anthocyanin accumulation covered apple MdMYB10, MdMYB3, MdMYB24L, MdMYB308L, and MdMYB114 [29][30][31][32][33], strawberry FaMYB5 [34], peach PpMYB10.1 and PpMYB6 [35,36], Chinese bayberry MrMYB1 [37], Lily LvMYB5 and LvMYB19 [38,39], Pistacia chinensis PcMYB113 [40], and grapevine VvMYBA1 and VvMYBA2 [41,42]. Recent researches revealed that MdNAC42, a novel NAC transcription factor, interacts with MdMYB10 to modulate the anthocyanin level in red-fleshed apples.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that WD40 proteins are not necessary for regulating avonoid synthesis, and their main role may be in the response to external signals (Feng et al 2019). However, other studies have shown that the diversity of MBW functions is due to MYB, rather than the bHLH or WD40 transcription factors (Chagné et al 2013;Wang et al 2022;Hui et al 2019).…”
Section: Introductionmentioning
confidence: 99%